Comparative Analysis of Three Vertebral Screw Placement Directions in Anterior Thoracolumbar Fracture Surgery: A Finite Element Study - Xuehai Jia; Yanjun Xie; Yi Yang; Yi Deng; Kerui Zhang; Changyong Shen; Ya Li; Litai Ma (Orthopaedic Surgery)
ABSTRACT Background Thoracolumbar fractures, especially burst fractures, are common severe spinal injuries requiring surgery. The main goals are to restore spinal stability and normal curvature, relieve nerve compression, and prevent further neurological damage. Minimally invasive techniques are increasingly used in spinal surgery. This study aims to use finite element analysis to compare two new thoracolumbar anterior fixation systems: Hybrid cross‐thoracolumbar fixation system and new hybrid cross‐thoracolumbar fixation system (HXTL and NHXTL) with Medtronic's ANTERIOR system, providing a theoretical reference for surgeries. Method A finite element model of the T12–L2 vertebrae of a 27‐year‐old healthy male was built based on CT images. The model was processed, optimized, meshed, and analyzed using software. In vitro biomechanical tests were compared with the finite element model results to verify the model's validity. A 500 N compressive load and a 10 N m bending moment were applied to the upper surface of T12. The stress and displacement of the vertebral body and the stress state of the support body of the two models under various conditions like forward flexion and backward extension were observed and analyzed. Results The study compared the biomechanical performance of the HXTL, NHXTL, and ANTERIOR systems under six physiological conditions. The vertebral body displacement of the three systems was maximum under forward flexion. During right flexion, the HXTL displacement was significantly greater than that of the ANTERIOR and NHXTL systems, while during extension, the HXTL and NHXTL displacements were significantly less than those of the ANTERIOR system. Under other motion conditions, the displacements were relatively small. In terms of vertebral body stress, the ANTERIOR model had the maximum stress during left flexion, significantly greater than that of the other two. In terms of titanium mesh stress, the HXTL system had significantly higher stress during extension and left rotation compared to the other two systems. In terms of nail–rod stress, the ANTERIOR system had higher stress in all directions than the HXTL and NHXTL systems. Conclusion Compared with the ANTERIOR system, the HXTL system reduces the surgical incision through oblique nail placement, can reduce the risk of nail–rod failure, and increase the stability of the titanium mesh between vertebral bodies, but it also brings a higher risk of subsidence. The NHXTL model not only reduces the surgical incision and the risk of accidental injury to contralateral blood vessels but also reduces the risk of nail–rod failure and does not increase the risk of titanium mesh subsidence. It is a more optimized choice.